KINERJA BUMDES DALAM RANGKA PENINGKATAN KESEJAHTERAAN MASYARAKAT DESA - Israwati Akib (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
In order to create the welfare of rural communities throughout Indonesia, the government gives trust to business entities to be able to manage natural resources in the village to serve as a form of business that can improve the welfare of the village community. This study aims to analyze the performance of Bumdes in order to improve the welfare of rural communities. This study uses a qualitative descriptive method with data collection techniques through observation, interviews and literature study. The results of the study indicate that the performance of Bumdes has not been able to run optimally because the human resources driving the BUMDes are inexperienced and professional in managing the business, this is indicated by the fact that there are still many poor people in the village.